2015
DOI: 10.1093/mnras/stv1377
|View full text |Cite
|
Sign up to set email alerts
|

Is the radio emission in the Bullet cluster due to dark matter annihilation?

Abstract: We study the complex structure of the Bullet cluster radio halo to determine the Dark Matter (DM) contribution to the emission observed in the different subhalos corresponding to the DM and baryonic dominated regions. We use different non-thermal models to study the different regions, and we compare our results with the available observations in the radio, X-ray and gamma-ray bands, and the Sunyaev-Zel'dovich (SZ) effect data. We find that the radio emission coming from the main DM subhalo can be produced by s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…In the hard X-ray and soft gamma-ray bands the emission coming from DM-produced electrons is well below the sensitivity of the next generation and/or proposed instruments like Astro-H2 or AstroMeV and ASTROGAM (Colafrancesco & Marchegiani, in preparation): however, a possible detection of galaxy clusters in these bands can be used to rule out DM models. The same is true for the microwave band, where DM models do not provide a strong non-thermal Sunyaev-Zel'dovich effect (SZE) signal because they produce a very low amount of electrons at low energies (see, e.g., [34]); therefore, a possible detection of the non-thermal SZE in Coma would allow to exclude a DM origin for the non-thermal electrons.…”
Section: Discussionmentioning
confidence: 97%
“…In the hard X-ray and soft gamma-ray bands the emission coming from DM-produced electrons is well below the sensitivity of the next generation and/or proposed instruments like Astro-H2 or AstroMeV and ASTROGAM (Colafrancesco & Marchegiani, in preparation): however, a possible detection of galaxy clusters in these bands can be used to rule out DM models. The same is true for the microwave band, where DM models do not provide a strong non-thermal Sunyaev-Zel'dovich effect (SZE) signal because they produce a very low amount of electrons at low energies (see, e.g., [34]); therefore, a possible detection of the non-thermal SZE in Coma would allow to exclude a DM origin for the non-thermal electrons.…”
Section: Discussionmentioning
confidence: 97%
“…It is anyway possible that the DM can give a contribution in some regions of the cluster, as suggested in the case of the Bullet cluster [5]. In the next Section we explore this possibility.…”
Section: Radio Emission In the Whole Clustermentioning
confidence: 87%
“…However, other mechanisms originated by ordinary matter (baryonic or leptonic) can produce non-thermal emission in galaxy clusters [3]. In clusters where the DM density spatial distribution, as derived from gravitational lensing measures, is different from the Intra Cluster Medium (ICM) one, as derived from X-rays, like for example in the Bullet cluster [4], the detection of DM-induced signals can be easier in the cluster regions where the DM is supposed to be dominant [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Colafrancesco, Marchegiani & Palladino, 2003). A non-thermal contribution to the total SZE has been possibly detected in the Bullet cluster (Colafrancesco, Marchegiani & Buonanno, 2011;Marchegiani & Colafrancesco, 2015), suggesting the possibility of a very small value of the minimum energy of the electrons (γ min ∼ 1.4). Also, a statistical study of the SZE in 23 radio halo clusters (Colafrancesco et al, 2014) suggested an average value of the ratio between non-thermal and thermal electrons pressures of the order of X ≡ P non−th /P th ≈ 0.55.…”
Section: Introductionmentioning
confidence: 98%